Repair Method for Complete High Ulnar Nerve Injury Based on Nerve Magnified Regeneration - Ding W; Li X; Pan J; Zhang P; Yin S; Zhou X; Li J; Wang L; Wang X; Dong J (Dove Medical Press, 2020)
Wenquan Ding,1,* Xueyuan Li,1,* Jiadong Pan,1 Peixun Zhang,2 Shanqing Yin,1 Xianting Zhou,1 Junjie Li,1 Liping Wang,1,3 Xin Wang,1 Jianghui Dong1,3 1Department of Hand Surgery, Department of Plastic Reconstructive Surgery, Ningbo No. 6 Hospital, Ningbo 315040, People’s Republic of China; 2Department of Trauma Orthopedics, Peking University People’s Hospital, Beijing 100044, People’s Republic of China; 3School of Pharmacy and Medical Sciences, and UniSA Cancer Research Institute, University of South Australia, Adelaide, SA 5001, Australia*These authors contributed equally to this workCorrespondence: Xin WangDepartment of Hand Surgery, Department of Plastic Reconstructive Surgery, Ningbo No.6 Hospital, Ningbo 315040, People’s Republic of ChinaTel/Fax +86574-87996193Email dr.wangxin@hotmail.comJianghui DongSchool of Pharmacy and Medical Sciences, University of South Australia, Adelaide SA 5001, AustraliaTel +618 8302 2715Fax +618 8302 1087Email Jianghui.dong@mymail.unisa.edu.auPurpose: Complete high ulnar nerve injury can cause serious sequelae, including residual sensation and loss of movement and especially dysfunction of the intrinsic muscles of the hand. As a solution to treat complete high ulnar nerve injury, we proposed a new repair method for ulnar nerve injury based on nerve-magnified regeneration.Methods: Twenty-two patients with complete division of the ulnar nerve at a high level who were treated from May 2013 to December 2016 were divided into two groups. The proposed repair method for complete high ulnar nerve injury was performed in group I (11 patients), while the traditional repair method, ie, repair of the original injury site of the ulnar nerve, was used in group II (11 patients).Results: The results showed no significant difference in the mean sensory scores assigned by the Highet-Zachary scheme (the Highet Scale) between the two groups. The mean Highet Scale score of muscle strength for the first dorsal interosseus muscle was significantly better in group I than that in group II (p=0.010). In group I, 10 of 11 patients were graded as M4 or M5. Grip strength, pinch strength, and the Disabilities of the Arm, Shoulder, and Hand (DASH) score were significantly better in group I than those in group II (p< 0.01).Conclusion: Therefore, this method for complete high ulnar nerve injury based on nerve-magnified regeneration can shorten the path of motor nerve regeneration, effectively reduce atrophy of the intrinsic muscles of the hand, and provide better hand function.Keywords: nerve magnified regeneration, ulnar nerve injury, nerve repair, peripheral nervous system